Growth and branching habit of rooted cuttings collected from epicormic shoots of Betula pendula Roth - Cameron, A.D.; Hamsawi, Sani (Oxford University Press, 1994)
Patterns of shoot growth and branching were studied over two growing seasons in rooted cuttings collected from both epicomric shoots and seedlings of Betula pendula Roth. Epicormic shoots were induced to sprout on stumps and small logs of 5-, IO- and 30.year-old trees. The use of epicormic shoots enhanced the rooting capacity of stem cuttings collected from these shoots but did not appear to reverse the process of maturation. In this study, maturation was based on characteristics typical of mature trees but not necessarily those of the mother plant, because it was not possible to root cuttings, for comparison, from 5-, lo- and 30-year-old ortets, other than from epicormic shoots. There was evidence of the persistence of mature characteristics through an increase in shoot plagiotropism with increasing ortet age. Rooted cuttings from both seedlings and epicormic shoots, however, assumed an increasingly orthotropic habit with a smaller shoot angle at the end of the first growing season than at the beginning and this continued into the second growing season. Other indications of maturation, such as delayed bud flushing and the incidence of flowering with increasing ortet age, were also evident in rooted cuttings from epicormic shoots. There was a clear difference in branching habit depending on cutting source. Rooted cuttings derived from epicormic shoots produced nearly twice as many lateral branches compared with rooted cuttings collected from seedlings, but this was not an effect of maturation. There was some evidence that rooted cuttings derived from seedlings grew taller than rooted cuttings from epicormic shoots.